Kebijakan Trans Metro Deli sebagai Upaya Meningkatkan Layanan Transportasi Umum di Kota Medan - Siti Khoiria (Journal on Education, 2024)
The Trans Metro Deli policy in Medan City is an effort to improve public transportation services. First, this policy provides an integrated and efficient mass transportation system through a special bus network with routes that cross strategic points in the city of Medan. Second, the adoption of information technology in the operational management of Trans Metro Deli allows users to obtain the latest information regarding bus schedules, routes and conditions in real-time, increasing reliability and user comfort. Apart from that, implementing affordable fares is also an important point in this policy, expanding transportation accessibility for people from various economic layers. Third, the Trans Metro Deli policy also prioritizes safety and security aspects in the use of public transportation by establishing operational standards and strict supervision of the bus fleet and personnel. This has a positive impact on public perception and trust in the service. Furthermore, efforts to improve infrastructure including the development of special bus stops and lanes are also an important part of this policy, ensuring accessibility and efficiency in daily operations. In conclusion, the Trans Metro Deli policy in Medan City is a significant step in improving public transportation services by integrating various aspects such as operational efficiency, use of technology, safety, comfort and accessibility. In this way, it is hoped that it can have a broad positive impact on the mobility and quality of life of city residents.